Improvement of Soil Chemistry Characteristic of Upland with Rock Phosphate, Phosphate-Solubilizing Bacteria and Farm Yard Manure For Increase of Soybean Yield - Noor, Aidi (UNIVERSITY OF LAMPUNG, 2008)
The experiment aims to know the role of rock phosphate, phosphate-solubilizing bacteria and farm yard manure application in improve quality of acid upland and its influence to soybean yield. Experiment was conducted in the greenhouse using Ultisols from Kentrong at 2001 year. Factorial experiment design with two factors was used in randomized complete block design with three replications. The first factors was rock phosphate dosages i.e. : 0; 30; 60; 90 kg P ha-1, and the second factor was combination of phosphate solubilizing bacteria (PSB) and farm yard manure (FYM) i.e. : without PSB and FYM (control); PSB (Pseudomonas fluorescens); FYM 10 t ha-1, and PSB+FYM. Results indicated that rock phosphate and combination of PSB and FYM application increased available P and decrase exchangeable Al of soils, increase nutrient uptake N, P, nodulation and grain yield of soybean. Application of phosphate solubilizing bacteria and farm yard manure combination with rock phosphate 30 kg P ha-1 dosages average increase grain yield soybean 23.5% compared with control. Grain yield of soybean 87% affected by variables of available P soils (X1), nutrient uptake N (X4) and P (X5), with multiple regression equation : Y = 0.241 + 0.03900 X1 + 0.00470 X4 + 0.04263 X5.